Формування базових компетенцій бакалаврів з машинобудування при вивченні природничих дисциплін - Асєєва, Ірина Володимирівна; Пономарьов, Олександр Семенович (Харківський національний університет імені В. Н. Каразіна, 2018)
Розкрито значення розвитку професійної компетентності майбутніх бакалаврів машинобудівних спеціальностей у забезпеченні якості їх професійної діяльності і життєвого успіху. Наведено загальну структуру базової професійної компетентності. Детально проаналізовано склад системи базових компетенцій та її основних компонентів. Показано вплив вивчення бакалаврами природничо-наукових дисциплін на формування базової професійної компетентності, значення інтересу студентів до навчання та отримання якісної освіти.

The importance of developing professional competence of bachelors of machine engineering specialties in ensuring the quality of their professional activity and life's success is studied. Professional competence in the field of higher education pedagogy is viewed as an integral system unity of key, basic and special competencies. The essence and content of the concept of basic professional competence are determined. The general structure and a detailed analysis of the basic competencies and their main components are presented. An analysis of the general structure of basic competences gives an idea of their essence and content. Key competencies are related to the willingness and ability of a specialist to self-study, with his or her flexibility in the relationship with people including employers, with his or her ability to represent and ensure an adequate level of success in a modern competitive environment. The basic competencies are aimed at helping to build such activities in the general context of social requirements for goals, content and character. Special competencies may be considered as a specific implementation of key and basic competences in a particular area of professional activity. It is determined that all three types of competence considered are interrelated and form a certain systemic integrity. It is shown that the structure of the totality of these competences should include such interrelated components: motivational, personal, purposeful, communicative, cognitive, reflexive and organizational. The influence of studying natural science disciplines on the formation of basic professional competence of bachelors, the importance of students' interest in learning and motivation to obtain quality education is shown. A clear statement of the goals of the educational process of professional preparation in general and the study of natural science disciplines in particular should be used to ensure the proper development of the basic competencies system of a specialist.
Forming basic competencies of bachelors of machine engineering in studying natural science disciplines
Keywords: професійна компетентність; базові компетенції; компоненти базових компетенцій; навчально-виховний процес; природничо-наукові дисципліни; бакалаври; машинобудування; professional competence; basic competences; components of basic competences; educational process; natural science disciplines; bachelor; machine en gineering